Association of railway industry occupations with hypertension - E. A. Zhidkova; V. B. Pankova; M. F. Vilk; K. G. Gurevich; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2021)
The review considers the issues of the association of railway industry occupations with the hypertension (HTN) risk. There is a number of reviews have been published earlier, where the high prevalence of HTN in railway workers was mentioned. Scientific literature was studied using the following keywords: “railway” and “hypertension” both in Russian and in English. A large spread in HTN prevalence among footplate staff was revealed according to different sources — from 7 to 60%. When recalculating the literature data on HTN prevalence among footplate staff in the CIS unites, it turned out to be no higher than that obtained for working-age men according to the Epidemiology of Cardiovascular Diseases and their Risk Factors in Regions of Russian Federation (ESSE-RF). A number of studies indicate that HTN is developing faster for locomotive drivers than for people not working in the railway industry. In our opinion, scientific work on the high frequency of HTN among railway workers can only be considered preliminary. Probably, the development of HTN could be influenced not only by occupational, but also by the major risk factors, such as metabolic ones, obesity, etc.